TANTANGAN GURU DALAM MENINGKATKAN PERKEMBANGAN LITERASI AWAL ANAK DALAM KONTEKS PEMBELAJARAN DEEP LEARNING DI PENDIDIKAN DASAR: ANALISIS KASUS KESULITAN PENGENALAN HURUF - Muhajanah; Berlian Adi Nugroho; Indah Lestari; Moch.Widjanarko (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research analyzes the challenges teachers face in enhancing early literacy development among elementary school students within the context of deep learning pedagogy, focusing on a case study of letter recognition difficulties. Conducted at SD Negeri 3 Tempur, this qualitative case study examines a first-grade student who demonstrates an atypical literacy profile: the ability to "read" words with visual-picture support and copy written letters accurately, yet significant struggles with abstract letter recognition and differentiation. Through comprehensive observation and assessment, the study explores the cognitive, social-emotional, and psychological developmental dynamics of this learning pattern. Findings reveal that the student exhibits stronger dependence on visual-semantic processing pathways rather than phonological-alphabetic routes, experiencing particular difficulties with mirror-image letters and lacking phonological awareness development. The research identifies that deep learning approaches emphasizing symbolic processing without multimodal support may exacerbate early literacy gaps for children with non-typical literacy profiles. Based on Piaget's and Vygotsky's developmental theories, along with Dual Coding Theory, this study recommends comprehensive multi-component interventions including explicit phonological awareness instruction, multisensory letter recognition methods, individualized scaffolding, and close collaboration among teachers, parents, and professional specialists to support inclusive literacy development.